Development and validation of a UV–Vis spectrophotometric method for estimation of total content of chalcone - J.R.S. Botelho; A. Caeiro; H.C. Sousa; M.E.M. Braga; M.G. Campos (MethodsX)
In this study, a straightforward spectrophotometric method was developed for quantifying the total content of chalcones in a sample. The method exhibits linearity, accuracy, precision, repeatability, and enables the estimation of total chalcone content in trans-chalcone equivalents for a sample diluted in carbon tetrachloride and added to antimony pentachloride. The analytical wavelength was determined to be 390 nm. Linearity was observed within the concentration range of 0.3 to 17.6 µg/mL of trans-chalcone in CCl4, with a R2 of 0.9994 and a random dispersion of the residual concentrations. In the accuracy study, recoveries ranged from 98 to 102 %. In the inter-day precision study, the compared data showed no statistically significant differences based on p-values from Student's t-test and the two-tailed Kruskal-Wallis test. In the repeatability study, the coefficients of variation were 1.92 % and 2.08 %. Additionally, this method is specific for trans-chalcone in the presence of the flavanol (+)-catechin, the flavone luteolin, and the flavonol quercetin. The total content of chalcone was estimated for plant extracts in trans-chalcone equivalents (tCe). The total content of chalcones in these extracts ranged from non-detected up to 22 % of tCe. Therefore, this method can be used for the initial estimation of the overall chalcone content.